Aspecte psihologice ale îngrijirii paliative [Articol] - Praviţchi, Galina (CEP USM, 2010)
Palliative care is a concept of care that combines a number of measures, treatments aimed to improve quality of life of sufferers of incurable diseases that endanger their lives and their families as well. On the basis of this concept lies the belief that every person is entitled to be treated well and to die with dignity. Relieving physical pain, emotional and social needs is an essential human right and is so focused on the patient, as well as on his family affected by serious illness of one of its members. The basic element is to alleviate pain from any source: the physical, psychological, spiritual, social and providing support to those who care to overcome their emotions and troubles. Psychological support for patients and their families includes counseling on psychological and mental condition of the patient, friends and family counseling, psychological support given to the patient and family members, guidance to support groups, respecting confidentiality, supporting after death, development and introduction of initiatives aimed at psychological support, treatment of disease caused by psychological disorders such as depression and anxiety, so the risk of suicide.
Keywords: Îngrijire paliativă